Knowledge, attitudes, and beliefs regarding acute coronary syndrome in patients with type 2 diabetes: a cross-sectional study - Mohammad Amerzadeh; Mahdie Bahrami; Mojtaba Senmar; Zahra Hosseinkhani; Zahra Shafiei Kisomi (Discover Public Health)
Abstract Introduction Cardiovascular diseases are one of the leading causes of mortality and disability among individuals with diabetes. Cardiac mortality in these patients is often associated with the prevalence of silent ischemia. Increasing awareness and changing patient behaviors and attitudes can reduce disease-related mortality. Therefore, this study aimed to determine the knowledge, attitudes, and beliefs regarding acute coronary syndrome in patients with type 2 diabetes mellitus (T2DM). Methods This cross-sectional study was conducted on 303 diabetic patients attending the Velayat and Bou Ali hospitals in Qazvin, Iran, in 2024. Inclusion criteria included a willingness to participate in the study, mental health status (based on existing records), and no history of myocardial infarction (MI). Data collection tools comprised a demographic questionnaire and the ACS Response questionnaire. Data analysis was performed using descriptive and analytical statistics, with a significance level of <0.05 for all tests. Results The mean (standard deviation) scores for knowledge, attitudes, and performance of patients with T2DM were 67.46 (6.3), 62.11 (28.2), and 97.22 (5.4), respectively. In the knowledge section, the highest percentage of correct responses was related to awareness of facilities in the hospital to reduce heart attack-related damages (62.3%) and familiarity with the symptoms of arm or hand numbness (43.41%). Patients had a low attitude towards heart disease, with approximately 36.4% being somewhat or completely confident in their ability to assist others with a heart attack. Regarding performance, 45.7% of individuals believed that they should promptly go to the hospital during a heart attack. Additionally, 44.2% preferred others to transport them to the hospital during a heart attack instead of using an ambulance. Conclusion Our findings indicate that patients with T2DM lack sufficient knowledge, attitudes, and beliefs regarding the symptoms of acute coronary syndrome (ACS). Although ACS manifests through various symptoms, patients in this study primarily identified chest pain, arm pain, and shortness of breath as indicators of ACS. At the same time, over half of the participants were unaware of other symptoms. Therefore, it is essential to educate individuals about the full range of potential ACS symptoms.